2020
DOI: 10.3390/ijerph17072307
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological Stress Response in an Underwater Evacuation Training

Abstract: Background: This research aimed to analyze the psychophysiological stress response of air crews in an underwater evacuation training. Materials and Methods: We analyzed in 36 participants (39.06 ± 9.01 years) modifications in the rating of perceived exertion (RPE), subjective stress perception (SSP), heart rate (HR), blood oxygen saturation (BOS), cortical arousal (critical flicker fusion threshold, CFFT), heart rate variability (HRV), spirometry, isometric hand strength (IHS), and short-term memory (ST-M) bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…The rate of perceived exertion of the military participants was also higher than that of the control participants, probably due to the physical demands of their different roles during the flights, in line with the decrease in the FEV1, PEF, and urine proteins [1,5,7]; as the control did not perform any activity during the flights, the perceived exertion was lower. On the other hand, we found a significant decrease in the HR of the military participants in flights due to the experience, special training, and habituation to the flight stress, as other studies have previously shown [1,6,9,28,29]. We also found a significant decrease in cortical arousal in the control participants, but not in the military participants.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The rate of perceived exertion of the military participants was also higher than that of the control participants, probably due to the physical demands of their different roles during the flights, in line with the decrease in the FEV1, PEF, and urine proteins [1,5,7]; as the control did not perform any activity during the flights, the perceived exertion was lower. On the other hand, we found a significant decrease in the HR of the military participants in flights due to the experience, special training, and habituation to the flight stress, as other studies have previously shown [1,6,9,28,29]. We also found a significant decrease in cortical arousal in the control participants, but not in the military participants.…”
Section: Discussionsupporting
confidence: 80%
“…Independently of the combat situation, in military deployments, there are unpredictable and unknown hazards that elicit a stress response in the organism [2]. This response activates the fight-flight system and the physiological mechanisms that are basic to survival, also affecting cognitive processes, such as information processing, memory, perception, attention, judgement, and decision-making, as well as physical aspects, such as endurance, strength, and flexibility [1,[3][4][5][6]. The continuous exposure to the combat stressors of military populations and air force crews have been previously related with mental disorders, such as post-traumatic stress disorder (PTSD) [7], highlighting the importance of personalized training based on a better understanding of the psychological and physiological responses involved in stress coping mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two of these measures, which focus the methodological attention of this research due to its great potential in the study of this topic, are the Critical Flicker Fusion Threshold (CFFT), evaluated using one Flicker Fusion instrument ( Vicente-Rodríguez et al, 2020 ), and the DC Potential, evaluated using the OmegaWave technology. The neuro-physiological basis of flicker perception is complex but well established ( Görtelmeyer and Zimmermann, 1982 ).…”
Section: Introductionmentioning
confidence: 99%